Sosialisasi Smart Parenting di Era Digital pada Perkumpulan Perempuan Kawanua Kota Jayapura : Socialization of Smart Parenting in the Digital Era at the Kawanua Women's Association in Jayapura City - Padwa, Alfred Ayub Moses; Abidjulu, Fitrine Christiane; Saa, Septinus; Idris, Usman (Assoeltan: Indonesian Journal of Community Research and Engagement, 2025)
This community service initiative was motivated by the low capacity of residents to identify, plan, and implement solutions to their social environmental problems, particularly in the context of improving the quality of education and community empowerment. The objective of this activity was to strengthen the community's ability to conduct needs analysis, formulate action programs, and build sustainable collaboration between residents, schools, and local stakeholders. The method used was Participatory Action Research (PAR), which involves a reflection-action-evaluation cycle through focus group discussions, participant observation, local asset mapping, and collaborative workshops. The results of the community service demonstrated a significant increase in community engagement, the emergence of local initiatives based on real needs, and the formation of a more focused and sustainable joint action plan. Furthermore, the strengthened community capacity was evident in their ability to identify problems, develop solution strategies, and conduct independent evaluations of their activities. In conclusion, the PAR approach was effective in promoting community empowerment and independence. The main contribution of this service lies in its replicable collaborative model, strengthening social networks, and improving the quality of participatory program planning.